Environmentally friendly biosorbents (husks, pods and seeds) from Moringa oleifera for Pb(II) removal from contaminated water - Tavares, Fernanda Oliveira (Environmental technology, 2017)
Lead is a heavy metal considered highly toxic, responsible for causing several health problems as well as being extremely harmful to fauna and flora. Given this fact, several techniques have been studied for the removal of this metal from contaminated water, in which stands out adsorption. In this sense, the objective of this study was to evaluate the potential of lead(II) biosorption from contaminated water by seed husks, seeds and pods of Moringa oleifera Lam (moringa). Biomass was characterized by energy-dispersive X-ray spectroscopy, Scanning Electron Microscopy and Fourier transform infrared spectroscopy analyses. From the studied parameters, the optimal conditions obtained for the three analyzed biosorbents are: 30 min to equilibrium, pH 6 and 25°C temperature. The pseudo-second-order kinetic model was the best fitted to the experimental data for the three evaluated biosorbents. Regarding the adsorption isotherms, the model that best fitted to the experimental data for seed and seed husk was that proposed by Freundlich, and for the pod the Langmuir model. The analysis of the obtained thermodynamic data showed that the adsorption process is favorable and of exothermic nature. Through the results it was concluded that the evaluated biosorbents are efficient in lead(II) biosorption